"At 80 I Know Myself": Embodied Learning and Older Adults' Experiences of Polypharmacy and Perceptions of Deprescribing. (December 2019) - Ross, Alison; Gillett, James
In response to the risks of polypharmacy for older adults, there are increasing calls for the development and implementation of deprescribing programs. This article examines the forms of expertise that inform older adults' decisions about how to use medications given concerns over polypharmacy and a clinical focus on deprescribing. In-depth interviews with older adults found that diverse knowledge sources underpin decisions regarding polypharmacy and deprescribing. Findings indicate that this knowledge is formed through a lifetime of embodied learning—the production of relevant knowledge through lived experiences of the body. By way of this embodied learning, older adults possess individualized knowledge bases that inform health and health care decisions, especially regarding the use of medications. If deprescribing programs are to be embedded into standard preventive medical care of older adults, then it is valuable for health care providers to be aware of and take seriously the contribution of embodied knowledge.